Laser Evoked Potentials in Early and Presymptomatic Huntington’s Disease - Marina de Tommaso; Giovanni Franco; Katia Ricci; Anna Montemurno; Vittorio Sciruicchio (Behavioural Neurology)
Pain was rarely studied in Huntington’s disease (HD). We presently aimed to extend our previous study on pain pathways functions by laser evoked potentials (LEPs) to a larger cohort of early unmedicated HD patients and a small group of presymptomatic HD (PHD) subjects. Forty-two early HD patients, 10 PHD patients, and 64 controls were submitted to LEPs by right-hand stimulation. Two series of 30 laser stimuli were delivered, and artifact-free responses were averaged. The N1, N2, and P2 latencies were significantly increased and the N2P2 amplitude significantly reduced in HD patients compared to controls. In the HD group, the LEPs abnormalities correlated with functional decline. PHD subjects showed a slight and insignificant increase in LEPs latencies, which was inversely correlated with the possible age of HD clinical onset. Data of the present study seem to suggest that the functional state of nociceptive pathways as assessed by LEPs may be a potential biomarker of disease onset and progression. The assessment of pain symptoms in premanifest and manifest HD may also open a new scenario in terms of subtle disturbances of pain processing, which may have a role in the global burden of the disease.